2021
DOI: 10.1002/mrm.28652
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 13C MRI of hyperpolarized [1‐13C]pyruvate and lactate with the corresponding mass spectrometry images in a murine lymphoma model

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In contrast, a mass spectrometry imaging study on EL4 tumor sections showed that there was no correlation between the distribution of 13 C-labeled and unlabeled lactate in the tumors. However, there was a strong correlation between labeled pyruvate and lactate in the corresponding 13 C MR images acquired in vivo, suggesting that in the EL4 tumor, pyruvate delivery is more important [ 37 ]. The relative importance of pyruvate delivery and transport and lactate dehydrogenase activity in determining the rate of hyperpolarized 13 C label exchange between pyruvate and lactate appears to vary between different tumor types.…”
Section: In Vitro and In Vivo Experiments With Hp 13 ...mentioning
confidence: 99%
“…In contrast, a mass spectrometry imaging study on EL4 tumor sections showed that there was no correlation between the distribution of 13 C-labeled and unlabeled lactate in the tumors. However, there was a strong correlation between labeled pyruvate and lactate in the corresponding 13 C MR images acquired in vivo, suggesting that in the EL4 tumor, pyruvate delivery is more important [ 37 ]. The relative importance of pyruvate delivery and transport and lactate dehydrogenase activity in determining the rate of hyperpolarized 13 C label exchange between pyruvate and lactate appears to vary between different tumor types.…”
Section: In Vitro and In Vivo Experiments With Hp 13 ...mentioning
confidence: 99%
“…The technique used and the cancer‐specific biomarkers identified could serve as the basis for new diagnostic strategies for prostate cancer categorization. Numerous other AIMS techniques have been applied to detect cancer‐related biomarkers in biological samples, including PESI for the detection of colorectal liver metastasis 27 and DESI for prostate cancer and lymphoma detection 28,29 …”
Section: Applications Of Ambient Ionization Mass Spectrometrymentioning
confidence: 99%
“…Numerous other AIMS techniques have been applied to detect cancer‐related biomarkers in biological samples, including PESI for the detection of colorectal liver metastasis 27 and DESI for prostate cancer and lymphoma detection. 28 , 29 …”
Section: Applications Of Ambient Ionization Mass Spectrometrymentioning
confidence: 99%